2004
DOI: 10.1091/mbc.e04-04-0340
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Yeast Forkhead-associated Cell Cycle Transcription by Oxidative Stress

Abstract: The effects of oxidative stress on yeast cell cycle depend on the stress-exerting agent. We studied the effects of two oxidative stress agents, hydrogen peroxide (HP) and the superoxide-generating agent menadione (MD). We found that two small coexpressed groups of genes regulated by the Mcm1-Fkh2-Ndd1 transcription regulatory complex are sufficient to account for the difference in the effects of HP and MD on the progress of the cell cycle, namely, G1 arrest with MD and an S phase delay followed by a G2/M arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
65
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 68 publications
7
65
0
1
Order By: Relevance
“…5). Segments I, II, and IV are the time frames that cell cycle analyses indicated the G1, S, G2/M phases predominated (27). Also note that GOALIE accurately determined the length of peroxide treatment.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…5). Segments I, II, and IV are the time frames that cell cycle analyses indicated the G1, S, G2/M phases predominated (27). Also note that GOALIE accurately determined the length of peroxide treatment.…”
Section: Resultsmentioning
confidence: 89%
“…Cell cycle analysis of this segment indicated that the percent contribution of each phase of the cell cycle were approximately the same. MD treatment results in G1 arrest (27), and the segmentation obtained by GOALIE corresponded to the G1, S, G2/M, and G1 phases of the cell cycle (four segments), with accurate identification of entry into G1 arrest (Fig. 5).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Briefly, H 2 O 2 (15) and menadione (16) are both inducers of oxidative stress, although their specific mechanisms of action vary. SP600125 (17) is a putative Jun N-terminal kinase (JNK) inhibitor, and diphenyleneiodonium (18) is a flavoprotein inhibitor.…”
Section: Resultsmentioning
confidence: 99%